Norway : Selected Issues. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper presents an assessment of Norway's inflation targeting framework. It describes the institutional framework, and reviews accountability and transparency of the central bank as well as its communication with the public. The paper discusses the design of the framework, and the monetary transmission. It concludes that the institutional framework is appropriate for successful implementation of monetary policy. The new framework provides a more flexible monetary regime that is consistent with Norway's overall economic policy framework.